Removable Orthodontic Appliance with Interproximal Reduction to Correct Mandibular Anterior Crowding - Rifda Muthia Sabrina; Bramita Beta Arnanda (Jurnal EduHealth, 2025)
Anterior crowding occurs due to a lack of coordination and disparity between tooth size and dental arch, resulting in available space limitation causing anterior tooth rotation and overlap. Removable orthodontic appliances combined with the Interproximal Reduction (IPR) technique have been used to correct anterior crowding. Case: A 26-year-old female came to Soelastri Dental and Oral Hospital of The Muhammadiyah Surakarta University with Angle Class I Dewey Type 1 malocclusion and individual dental malposition of maxillary and mandibular anterior (SNA 81°; SNB 78°; ANB 3°; overjet 3.3 mm; overbite 3.75 mm; convex profile). The treatment was carried out using removable orthodontic appliances combined with the IPR technique. Case Management: The Hawley appliances, consisting of labial arches and Adam clasps with active components were used for this case. A design modification of a U-shaped maxillary acrylic baseplate was made to free the torus on the palatal area. The IPR technique was done on the anterior teeth by slicing 0.25 mm for each side. The patient was instructed to use the appliances for 20 - 22 hours daily. Dental evaluation was scheduled every week to reactivate the springs. After 6 months, both mandibular canines were corrected and 41 showed significant movement mesiolabially. Conclusion: Patient compliance in wearing and maintaining the appliance could affect the correction of anterior crowding.